Room-temperature ferromagnetism observed in graphene oxide - Oh, DaYea; Park, Bae Ho; Lee, Duk Hyun; Kim, Wondong; Choi, Jun Woo (한국물리학회, 2023)
We investigate magnetic properties of graphene oxide flake that have been locally oxidized using atomic force microscope (AFM) lithography. This approach reduces the possibility of magnetic contamination. Our Raman spectroscopy analysis reveals that the graphene oxide contains crystalline defects or disorders and differs from the pristine graphene in terms of its atomic structure. Using magnetic force microscopy measurements, we observe that the graphene oxide has a net magnetization pointing out of the surface plane. Furthermore, our magneto-optical Kerr effect data show small but clear hysteresis loops with non-zero remanent magnetization. We also conduct x-ray magnetic circular dichroism (XMCD) photoemission electron microscope measurements and identify remarkable asymmetry in carbon K edge spectra, which strongly suggests that the observed ferromagnetic order in the graphene oxide layer is intrinsic. A careful analysis of XMCD signals depending on the oxidized condition reveals the effects of chemical states of carbon atoms on the formation of ferromagnetic order in the graphene oxide.